P140 Validation of EULAR/ACR 2019 classification criteria for SLE in a south Indian juvenile SLE cohort. (20th April 2020) - Nair, Harikrishnan Bhaskaran; Balan, Suma
Abstract: Background: To date there is no specific classification criteria for juvenile systemic lupus erythematosus (jSLE). Our aim is to compare the real world performance of EULAR/ACR 2019 criteria when applied to a known cohort of jSLE cases in Kerala, India. Methods: We retrospectively reviewed the electronic medical record of all patients (n = 735), admitted under the Pediatric Rheumatology Department, Amrita Institute of Medical Sciences, Kochi, a tertiary care center in Kerala, India, during the period January 2012 to June 2019. 107 patients were diagnosed with jSLE by a qualified experienced pediatric rheumatologist and were independently assessed by an adult rheumatologist. Every sixth patient of the remaining 628 patients were selected as the control (n = 105). Patients were excluded if the diagnosis was uncertain or, if there was an overlap with jSLE. Each patient was evaluated to see if he or she satisfied the ACR-1997, SLICC-2012, or EULAR/ACR- 2019 criteria. Results: Female: male ratio in cases and controls was 4.1:1 and 2.4 :1 respectively. Mean age for cases and controls was 12.6 +/-2.9 and 11.8 +/-3.5 respectively. The comparison of performance of each criterion is shown in table 1. Table 1: Validation of the EULAR/ACR 2019 SLE classification criteria using clinically diagnosed 107 jSLE cases. ACR- American College of Rheumatology; EULAR- European League Against Rheumatism; SLICC-Systemic Lupus International Collaborating Clinics; PPV- positive predictive value; NPV- negative predictive value Conclusion: The new EULAR/ACR 2019 criteria achieved sensitivity, specificity, PPV, NPV and accuracy greater than SLICC 2012 criteria. It also achieved sensitivity, NPV and accuracy greater than 1997 ACR criteria. Disclosures: H. Bhaskaran Nair None. S. Balan None.